Combining ATAC-seq with nuclei sorting for discovery of cis-regulatory regions in plant genomes. Issue 6 (28th November 2016) - Lu, Zefu; Hofmeister, Brigitte T.; Vollmers, Christopher; DuBois, Rebecca M.; Schmitz, Robert J.
Abstract: Chromatin structure plays a pivotal role in facilitating proper control of gene expression. Transcription factor (TF) binding of cis -elements is often associated with accessible chromatin regions. Therefore, the ability to identify these accessible regions throughout plant genomes will advance understanding of the relationship between TF binding, chromatin status and the regulation of gene expression. Assay for Transposase Accessible Chromatin sequencing (ATAC-seq) is a recently developed technique used to map open chromatin zones in animal genomes. However, in plants, the existence of cell walls, subcellular organelles and the lack of stable cell lines have prevented routine application of this technique. Here, we describe an assay combining ATAC-seq with fluorescence-activated nuclei sorting (FANS) to identify and map open chromatin and TF-binding sites in plant genomes. FANS-ATAC-seq compares favorably with published DNaseI sequencing (DNase-seq) results and it requires less than 50 000 nuclei for accurate identification of accessible genomic regions. Summary: Application of ATAC-seq to sorted nuclei identifies accessible regions genome-wide.